(untitled) (Research, Society and Development, 2020)
The environment started to have some attention only from the mid-60’s in Brazil and only after about 10 years began to emerge laws, programs or institutions of effect. The recovery of degraded ecosystems has been increasingly important given the increasingly drastic picture of the global environmental crisis and the implementation of programs for the recovery of degraded areas is of paramount importance. Degraded areas cause loss of production capacity of food, wood and other products, as well as loss or reduction of biodiversity. Given the need for intervention in degradation processes, less costly recovery techniques are emerging and one of these is the recovery of degraded areas by pasture. This measure, besides being technically and economically viable, would prevent the deforestation of native forests for the emergence of new pastures, as it would allow the use of those areas that became infertile longer. Based on this bibliographic survey, this paper aims to review the literature about the pasture recovery process.